Drivers of human-megaherbivore interactions in the Eastern and Western Ghats of southern India. (15th August 2022) - Ramesh, Tharmalingam; Milda, David; Kalle, Riddhika; Gayathri, V.; Thanikodi, M.; Ashish, K.; Giordano, Anthony J.
Abstract: The global effort to protect megaherbivore populations is largely dependent on how human-wildlife conflict is identified, prioritized, and remedied. We examined the socio-ecological and landscape-scale factors determining spatial patterns of human-megaherbivore (Asian elephant Elephas maximus and gaur Bos gaurus ) interactions across sixteen Forest Divisions in Tamil Nadu, India. Using a systematic grid-based design, we conducted questionnaire-based surveys of 1460 households at the human-wildlife interface adjacent to Protected Areas, Reserve Forest and Fringe Areas. We specifically collected information on elephant and gaur conflict incidents ( e.g., human death/injuries, property damage, and crop-raiding), cropland type, extent of crop area and area lost to crop-raiding, from each household. We found that human-elephant conflict increased with percentage of crop cover, diversity of major and minor crops grown, proximity to water source, flat terrain, and lower rates of precipitation. Human-gaur conflict was greatest with a high diversity of major crops, proximity to water source, moderate precipitation, and more undulating terrain. We identified ca. 7900 km 2 hotspot area of contiguous high-intensity elephant conflict. For gaur, we identified high-frequency conflict hotspot areas covering ca. 625 km 2, which were patchily distributed, highly localised, and attributed mostly to the recent changing land-use patterns. Our findings will help policymakers and park managers in developing landscape-scale human-wildlife conflict mitigation plans in the identified conflict hotspots. Highlights: We examined social-ecological landscape variables of human-megaherbivore interaction at interface areas. Elephant conflict associated to crop cover, crop diversity, water, low rainfall and low slope. Gaur conflict associated to major crop diversity, water, high rainfall and elevation. We identified 7900 km 2 and 625 km 2 prone to high elephant and gaur conflict respectively. Our findings underscore gradients of conflict hotspot areas for implementing mitigation measures.